1994
DOI: 10.1016/0735-1097(94)90853-2
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary doppler guide wire versus stress single-photon emission computed tomographic thallium-201 imaging in assessment of intermediate coronary stenosis

Abstract: In appropriately selected patients with intermediate coronary artery stenoses, Doppler guide wire determination of lesion significance provides equivalent data to those acquired by stress SPECT thallium-201 imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1
6

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(50 citation statements)
references
References 32 publications
4
39
1
6
Order By: Relevance
“…The correlation between percent area stenosis and CVR is improved only with high-grade stenoses. 4 In this respect, it is not surprising that a cutoff value for distal CVR around 2.0 indicates a hemodynamically significant epicardial coronary stenosis with high accuracy. Furthermore, it is not surprising that correlations between distal CVR measurements and thallium scintigraphy have been excellent, because both technologies evaluate the composite effect of blood flow reduction caused by the epicardial stenosis and by microvascular disease.…”
Section: Cvr Versus Rfvrmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between percent area stenosis and CVR is improved only with high-grade stenoses. 4 In this respect, it is not surprising that a cutoff value for distal CVR around 2.0 indicates a hemodynamically significant epicardial coronary stenosis with high accuracy. Furthermore, it is not surprising that correlations between distal CVR measurements and thallium scintigraphy have been excellent, because both technologies evaluate the composite effect of blood flow reduction caused by the epicardial stenosis and by microvascular disease.…”
Section: Cvr Versus Rfvrmentioning
confidence: 99%
“…[2][3][4][5] On the basis of this experience, intracoronary Doppler measurements are gaining more and more attention in clinical decision making. Smaller studies 6 as well as larger trials 7 have demonstrated that coronary interventions can be guided by physiological measurements and that the restenosis rate can be predicted on the basis of intracoronary Doppler measurements.…”
mentioning
confidence: 99%
“…[43][44][45]47,48 In fact, reversible defect on SPECT MPI was the best predictor of an abnormal fractional flow reserve 47 ( Figure 5). Multiple studies have demonstrated that CCTA has high sensitivity and that a "negative" study excludes the presence of hemodynamically significant coronary disease in most but not all patients compared with SPECT MPI.…”
Section: Hendelmentioning
confidence: 99%
“…Several trials examining stenoses of intermediate severity have noted poor correlation with physiological parameters ( Figure 5), such as predicted translesional gradients, 42 intracoronary assessment of coronary flow reserve, [43][44][45][46] and fractional flow reserve or exercise-induced ischemia. 46,47 The answer for improved correlation with physiology does not lie with quantification, leading to the conclusion by Fisher et al 46 that "Neither visual assessment of an angiography by experienced interventional cardiologists nor QCA can accurately predict the physiological significance of most moderate (40% to 70%) narrowings.…”
Section: Coronary Anatomy and Physiologymentioning
confidence: 99%
“…Strong correlations exist between myocardial stress testing and FFR or CVR (633,(638)(639)(640)(641)(642)(643)(644)(645)(646)(647)(648)(649)). An FFR of less than 0.75 identified physiologically significant stenoses associated with inducible myocardial ischemia with high sensitivity (88%), specificity (100%), positive predicted value (100%), and overall accuracy (93%).…”
Section: Coronary Artery Pressure Andmentioning
confidence: 99%